2019
DOI: 10.1029/2018jb017165
|View full text |Cite
|
Sign up to set email alerts
|

Mountain Building in Taiwan: Insights From 3‐D Geodynamic Models

Abstract: Taiwan is widely considered to be a typical example of an arc‐continent collision surrounded by two opposite dipping subduction zones. The manner by which the interaction of the two neighboring slabs caused plate collision and mountain building is insufficiently understood. Various hypotheses have been proposed, but the geodynamic feasibility of those remains to be tested. Here we present 3‐D thermomechanical models to study the geodynamic evolution process of a Taiwan‐like setting after an initial transform f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 95 publications
(196 reference statements)
7
13
0
Order By: Relevance
“…The present results generally coincide with previous findings, including isotropic tomography (e.g., Ai et al., 2019; Fan et al., 2016, 2015; T. Y. Huang et al., 2012; H. Huang et al., 2014; Koulakov et al., 2015, 2014; Kuo‐Chen et al., 2012; Toyokuni et al., 2016; Ustaszewski et al., 2012; Z. Wang et al., 2006; Zheng et al., 2013), seismic anisotropy (e.g., Fan & Zhao, 2019; B. S. Huang et al., 2006; T. Y. Huang et al., 2015; Koulakov et al., 2015; Kuo et al., 2018; Kuo‐Chen et al., 2009), and 3‐D thermomechanical modeling (e.g., X. X. Wang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The present results generally coincide with previous findings, including isotropic tomography (e.g., Ai et al., 2019; Fan et al., 2016, 2015; T. Y. Huang et al., 2012; H. Huang et al., 2014; Koulakov et al., 2015, 2014; Kuo‐Chen et al., 2012; Toyokuni et al., 2016; Ustaszewski et al., 2012; Z. Wang et al., 2006; Zheng et al., 2013), seismic anisotropy (e.g., Fan & Zhao, 2019; B. S. Huang et al., 2006; T. Y. Huang et al., 2015; Koulakov et al., 2015; Kuo et al., 2018; Kuo‐Chen et al., 2009), and 3‐D thermomechanical modeling (e.g., X. X. Wang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the northeastern, eastern, and southern edges of the Celebes Sea are bordered with several subduction zones, including the Cotabato and North Sulawesi subduction zones and the double‐sided subduction of the Molucca Sea plate (Figure 1). Numerical simulations have suggested that dynamic interactions take place in an active, complex tectonic setting composed of multiple subducting slabs (e.g., Király et al., 2016, 2018; Lyu et al., 2019; X. Wang et al., 2019). The upper mantle around the Celebes Sea is also proposed to have experienced a complex deformation history due to the subduction of multiple slabs in adjacent subduction zones (e.g., Di Leo et al., 2012a, 2012b; Király et al., 2018; Roy et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the simulated peak temperatures and pressure are determined to be 300°C and 0.5 GPa in the Backbone Range, 230°C and 0.32 GPa in the Hsuehshan Range, and 140°C and Lee et al (2015) shown and in Figure 9b2 computed from Fuller et al (2006). Temperature-time paths for tracers of (c1) profiles AA′ and BB′ in this study and (c2) profiles AA″ and BB″ in Wang et al (2019). The locations of the four profiles and the dashed lines are shown in Figure 9b.…”
Section: Hp Rock Exhumation In the Taiwan Orogenmentioning
confidence: 60%
“…The horizontal distance between the plate edges, which is represented by Dp at 70 km in all of the initial 3D double subduction-collision model setups, is sufficiently low to cause strong slab-slab interactions (Holt & Royden, 2020;Király et al, 2016Király et al, , 2021Peral et al, 2018;Wang et al, 2019). These interactions lead to different crustal deformation behaviors in the initial transform-fault region (Figures 3, 4, 6 and 7d).…”
Section: Channel Flow Modes and Slab Interactions In Opposite-dip Double Subduction-collision Systemsmentioning
confidence: 99%